Radiation-induced gliomas represent H3-/IDH-wild type pediatric gliomas with recurrent PDGFRA amplification and loss of CDKN2A/B - Deng, Maximilian Y; Sturm, Dominik; Pfaff, Elke; Sill, Martin; Stichel, Damian; Balasubramanian, Gnana Prakash; Tippelt, Stephan; Kramm, Christof; Donson, Andrew M; Green, Adam L; Jones, Chris; Schittenhelm, Jens; et al. (Nature communications, 2021)
Long-term complications such as radiation-induced second malignancies occur in a subset of patients following radiation-therapy, particularly relevant in pediatric patients due to the long follow-up period in case of survival. Radiation-induced gliomas (RIGs) have been reported in patients after treatment with cranial irradiation for various primary malignancies such as acute lymphoblastic leukemia (ALL) and medulloblastoma (MB). We perform comprehensive (epi-) genetic and expression profiling of RIGs arising after cranial irradiation for MB (n = 23) and ALL (n = 9). Our study reveals a unifying molecular signature for the majority of RIGs, with recurrent PDGFRA amplification and loss of CDKN2A/B and an absence of somatic hotspot mutations in genes encoding histone 3 variants or IDH1/2, uncovering diagnostic markers and potentially actionable targets.
Keywords: chromozomální delece; regulace genové exprese u nádorů; dospělí; záření; gliom; Kaplan-Meier Estimate; Female; genom lidský; dítě; Cyclin-Dependent Kinase Inhibitor p15; inhibitor p16 cyklin-dependentní kinasy; Adult; genová přestavba; Kaplanův-Meierův odhad; ženské pohlaví; mladý dospělý; Neoplasm Recurrence, Local; Gene Expression Regulation, Neoplastic; Adolescent; Cyclin-Dependent Kinase Inhibitor p16; Transcription, Genetic; inhibitor p15 cyklin-dependentní kinasy; shluková analýza; lidé; Radiation; metylace DNA; Glioma; genetická transkripce; Gene Amplification; Male; Receptor, Platelet-Derived Growth Factor alpha; Chromosome Deletion; Young Adult; DNA Methylation; lokální recidiva nádoru; Gene Rearrangement; lidé středního věku; Child; mužské pohlaví; Genome, Human; růstový faktor odvozený z trombocytů - receptor alfa; Cluster Analysis; amplifikace genu; Middle Aged; mladiství; Humans